2015
DOI: 10.1371/journal.pntd.0004023
|View full text |Cite
|
Sign up to set email alerts
|

Differential Host Immune Responses after Infection with Wild-Type or Lab-Attenuated Rabies Viruses in Dogs

Abstract: Rabies virus (RABV) induces encephalomyelitis in humans and animals. One of the major problems with rabies is that the infected individuals most often do not develop virus neutralizing antibodies (VNA). In this study we have investigated the host immune response to RABV infection in dogs, using a live-attenuated (TriGAS) or a wild-type (wt) (DRV-NG11) RABV isolated from a rabid dog.Methodology/Principal FindingsThe experimental infection of dogs with TriGAS induced high levels of VNA in the serum, whereas wt R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…G is the only viral protein exposed on the surface of the virion and plays an essential role in RABV pathogenicity (Lentz et al, 1983;Thoulouze et al, 1998). DRV-NG11 was shown to be highly virulent and caused 100% percent mortality in experimental dogs after intramuscular administration in a lower dose (Gnanadurai et al, 2015). To identify the differences of functional regions between DRV-NG11 and attenuated RABVs, their G protein sequences were aligned.…”
mentioning
confidence: 99%
“…G is the only viral protein exposed on the surface of the virion and plays an essential role in RABV pathogenicity (Lentz et al, 1983;Thoulouze et al, 1998). DRV-NG11 was shown to be highly virulent and caused 100% percent mortality in experimental dogs after intramuscular administration in a lower dose (Gnanadurai et al, 2015). To identify the differences of functional regions between DRV-NG11 and attenuated RABVs, their G protein sequences were aligned.…”
mentioning
confidence: 99%
“…It has been known for a long time that more than 70% human rabies patients do not develop VNA in the periphery as well as in the cerebrospinal fluid (CSF) at any stage. The same phenomenon, that wt RABV fails to induce protective VNA, is also observed in other animal species, such as mice, dogs and skunks [24][25][26] .…”
Section: Introductionmentioning
confidence: 53%
“…On the other hand, laboratory-attenuated RABV replicates rapidly and produces a large amount of the glycoprotein and induces strong innate and adaptive immune responses, such as extensive inflammation and neuronal apoptosis, expression of cytokines and chemokines, BBB permeability enhancement and DC activation as well as high level of VNA production [18,24,[27][28][29][30][31][32] . Numerous comparative studies performed in laboratory animals have suggested that the wt RABV evades, while laboratory-attenuated the RABV actives, the host innate immune responses [16,17,23,24,26,33] .…”
Section: Introductionmentioning
confidence: 99%
“…Actually, we detected strongly elevated expression of cytokines and chemokines in mice brains infected with GD-SH-01 at 6 dpi, which indicated that the mice got fatal encephalitis, and the infected mice did not recover from rabies till it died at 12 dpi (Gnanadurai et al, 2015;Miao et al, 2017). However, the brains infected with rHEP-SH-P presented a relatively low level of T cells and cytokine expression from day 6 due to the less permeability of BBB.…”
Section: Discussionmentioning
confidence: 90%
“…Although no significant difference between rHEP-SH-P and GD-SH-01 was detected in cerebella BBB permeability changes at 9 dpi, GD-SH-01 caused great increase in BBB permeability in comparison with control. By 12 dpi, BBB permeability increase in both cerebra and cerebella of mice infected with GD-SH-01 continued to be enhanced (more than threefold increase of NaF uptake); at this time point, majority of mice infected with GD-SH-01 developed severe neurological signs or died owing to rabies (Figures 2A,B), indicating that BBB was destroyed when rabies reached the final stage (Gnanadurai et al, 2015;Miao et al, 2017). However, the BBB of the mice infected with HEP-Flury recovered generally from transient breakdown, and those infected with rHEP-SH-P kept relative integrity in the course of infection.…”
Section: The Chimeric Rabv Strain Causes Less Enhancement Of Bbb Thanmentioning
confidence: 96%